Climacteric medicine: European Menopause and Andropause Society (EMAS) statements on postmenopausal hormonal therapy - Skouby, Sven O; Barlow, David; Samsioe, Göran; Gompel, Anne; Pines, Amos; Al-Azzawi, Farok; Graziottin, Allezzandra; Hudita, Decebal; Rozenberg, Serge (Maturitas, 2004)
Hormonal therapy (HT) is one of the most frequently prescribed drug regimens for women after the age of 50 years. HT has been developed progressively since the 1960s to provide estrogen to those women (a) who require relief of symptoms which have resulted from reduced circulating estrogen or (b) to act as an anti-resorptive agent to counteract the effect of the increased bone turnover which occurs with falling menopausal estrogen levels and which results in loss of bone mass leading to postmenopausal osteoporosis. However, a large number of women pass through the menopausal transition without experiencing distress as a result of the natural fall in estrogen hormone levels and since the introduction HT has been thought to be associated with a number of health benefits that have been tested in clinical trials but not substantiated. In women experiencing distressing climacteric symptoms double-blind randomised controlled clinical trials with a variety of HT regimens have shown that HT of any type provides symptom relief with no alternative treatment of similar effect. The dose and regimen of HT need to be individualised and in general the appropriate dose is dependent on the menopausal age. Women experiencing urogenital estrogen deficiency symptoms require long-term treatment which is most easily achieved with local estrogen. With the perspective provided by the most recent epidemiological findings not least from the estrogen only arm of the Women's Health Initiative Study (WHI) EMAS supports research activities generating HT with new compositions including lower doses and a wider range of progestins in order to positively affect the balance of clinical benefit and risk. Currently, however, individualized and appropriate prescription of the available HT products together with life-style management will sustain possibilities for beneficial effects on climacteric symptoms, quality of life and degenerative diseases after the menopause.
Keywords: Postmenopausal hormonal therapy; EMAS; Climacteric medicine; Position paper